Radiative heat transfer between spatially nonlocally responding dielectric objects. (23rd January 2018) - Schmidt, Robin; Scheel, Stefan
Abstract: We calculate numerically the heat transfer rate between a spatially dispersive sphere and a half-space. By utilising Huygens' principle and the extinction theorem, we derive the necessary reflection coefficients at the sphere and the plate without the need to resort to additional boundary conditions. We find for small distances d ∼ 1 nm a significant modification of the spectral heat transfer rate due to spatial dispersion. As a consequence, the spurious divergencies that occur in spatially local approach are absent.